The role of organic matter on suspended particulate matter dynamics in the Rhine region of freshwater influence - Safar, Zeinab; Chassagne, Claire; Rijnsburger, Sabine; Flores, Raúl P.; Pietrzak, Julie D.; Souza, Alejandro J.; van Kessel, Thijs; Horner-Devine, Alexander (Frontiers in Marine Science, 2025)
IntroductionIn this study we investigate the Suspended Particulate Matter (SPM) source and dynamics in terms of resuspension and advection in the mid field region of Rhine Region Of Freshwater Influence (Rhine-ROFI). In this area of the Rhine-ROFI, the sediment transport mechanisms are governed by the Rhine freshwater plume originating from the Rhine-Meuse estuary and propagating towards the coast in northward direction.MethodsThe SPM near the bottom at a mooring located at 12m of water depth is analyzed in terms of concentration, particle size and shape in correlation with frontal dynamics and weather conditions for two seasons of winter 2013 (12 February - 07 March) and autumn 2014 (17 September - 06 October).Results and discussionThe freshwater front transports organic matter (such as microalgae strains and other organic matter) from the estuary into the coastal area. In calm weather conditions in autumn, most particles in suspension are of low density and high anisotropy. These particles are recognized as elongated algae strains with some organic matter-clay aggregates (flocs), giving trimodal Particle Size Distributions (PSD). During the neap tides strong salinity stratification and low turbulence result in SPM accumulation at the bed forming a fluff layer. At spring tides a fast switch between stratified and well mixed water column conditions caused by tidal mixing results in resuspension of SPM. During spring tides, the PSD’s are multimodal at low bed stress (predominance of microalgae) and monomodal at high bed stress (predominance of mineral sediment). At the storm initiation in autumn, the organic-matter rich fluff layer is depleted in a matter of hours, which is reflected in the change in modality of the PSD’s. Once the resuspended material is dominated by the mineral clay fraction, the PSD turns sharply monomodal. During winter monomodal PSD’s are recorded during calm weather conditions. The particles in suspension are then relatively spherical flocs of low density. During the winter storm, the fluff layer, which is much thinner than in autumn, is depleted very fast. This study shows the importance of organic matter in the transport of mineral sediment particles in coastal areas. The dynamic composition of the fluff layer of the bed should be accounted for in erosion models.